Synthetic Aperture Radar Signal Simulation And Processing - Lim, Chee Siong (2008)
In this work, a MATLAB-based software program is developed to perform SAR image formation on both simulated and actual SAR data. Generally, the software program consists of three modules, namely SAR simulation module, actual SAR data extraction module, and SAR processing module.